Nano-liposomal zein hydrolysate for improved apoptotic activity and therapeutic index in lung cancer treatment - Sahand Mazloum-Ravasan; Maryam Mohammadi; Elaheh Madadi Hiagh; Alireza Ebrahimi; Joo-Hyun Hong; Hamed Hamishehkar; Ki Hyun Kim (Drug Delivery, 2022)
Lung cancer is one of the most common cancers in the world with a high mortality rate. Zein is a protein compound whose protein isolate is not useful and whose protein hydrolysis produces biological activity. By encapsulating this bioactive compound inside the nanoparticles (NPs), it causes itself to reach the tumor site and destroy it rapidly. In this study, the effects of zein hydrolysate (ZH) and nano-liposomal ZH (N-ZH) were investigated on the human A549 cell line. Western blotting and cell cycle analyses showed that ZH and N-ZH caused cytotoxicity. They induced apoptosis via cell cycle arrest at the G0 phase, as well as significant increases in pro-apoptotic genes, such as Bax, caspase-3, -8, -9, and p53, accompanied with significant decreases in the anti-apoptotic marker Bcl-2. Based on the results, the cytotoxic and anticancer effects of N-ZH were higher than those of free ZH. In conclusion, liposomes improved the performance of ZH and dramatically reduced the IC50 value of ZH. These findings provided the experimental evidence that N-ZH with favorable anticancer activity can be used as a therapeutic agent and strategy for lung cancer treatment in future clinical trials.